2011
DOI: 10.1007/s00421-010-1820-0
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill training prevents bone loss by inhibition of PPARγ expression but not promoting of Runx2 expression in ovariectomized rats

Abstract: Exercise training has been reported to prevent bone loss in ovariectomized (OVX) rats and postmenopausal women. We hypothesized that treadmill training inhibited adipogenesis and enhanced osteogenesis through the regulation of adipocyte differentiation factor peroxisome proliferators-activated receptor gamma (PPARγ) and the osteogenic factor runt-related transcription factor 2 (Runx2) in a model of OVX-induced osteoporosis. To test this hypothesis, 3-month-old female Sprague-Dawley rats were divided randomly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…Increased production of fat-related factors, such as fatty acids, could alter the fat-bone marrow relationship and inhibit hematopoiesis and/or osteogenesis [10]. Accumulating evidence from in vitro and in vivo studies suggests that the mesenchymal stem cell (MSCs) is the marrow precursor for adipocytes as well as osteoblasts [24][25][26][27]. The interaction between bone and fat formation is influenced by a multitude of factors including genetic, metabolic, and physical inputs to coordinate an appropriate adaptive response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased production of fat-related factors, such as fatty acids, could alter the fat-bone marrow relationship and inhibit hematopoiesis and/or osteogenesis [10]. Accumulating evidence from in vitro and in vivo studies suggests that the mesenchymal stem cell (MSCs) is the marrow precursor for adipocytes as well as osteoblasts [24][25][26][27]. The interaction between bone and fat formation is influenced by a multitude of factors including genetic, metabolic, and physical inputs to coordinate an appropriate adaptive response.…”
Section: Discussionmentioning
confidence: 98%
“…Activation of PPARγ positively regulates adipocyte differentiation while acting as a dominant negative regulator of osteogenic differentiation, inducing cells to shift to differentiated adipocytes. On the other hand Runx2 positively regulates osteogenic differentiation [25]. It is now known that oestrogen acts directly on both osteoblasts [28], osteoclasts [29].…”
Section: Discussionmentioning
confidence: 99%
“…As immobilization is known to be linked to increased bone loss, physical activity (or exercise) has been shown positive effect on bone health. Morever, Chen et al (2011) recently reported the involvement of PPARγ on bone mass using treadmill exercise in ovariectomized rats. These results demonstrated that CLA might improve bone health by modulating physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…138 This was also observed in ovariectomized rats given access to treadmill running: a reduction in MAT and prevention of bone loss. 139 While this inverse bone-to-fat relationship has been observed in several models, it is not always the case, as evidenced in certain mouse strains, such as C3H mice, which experience an increase in both bone and MAT. 78,140 However, while there was a suppression of PPAR-␥ , master regulator of adipogenesis, they did not observe an increase in RUNX2, master regulator of osteoblastogenesis, indicating that this relationship might not always be one-to-one.…”
Section: Exercise As a Treatment Modalitymentioning
confidence: 99%